Assessment of Flatfoot Deformity Using Digitally Reconstructed Radiographs: Reliability and Comparison to Conventional Radiographs. (July 2022) - Fuller, Robert M.; Kim, Jaeyoung; An, Tonya W.; Rajan, Lavan; Cororaton, Agnes D.; Kumar, Prashanth; Deland, Jonathan T.; Ellis, Scott J.
Background: Digitally reconstructed radiographs (DRRs) generated from weightbearing computed tomography (WBCT) may potentially substitute for weightbearing plain radiographs (XRs) but have not been clinically validated. This study aims to test the reliability of 6 radiographic parameters of progressive collapsing foot deformity (PCFD) as measured on DRR, to investigate whether DRR represents comparably to XR through the same measurements, and to compare agreement of DRR and XR measurements of a standardized arch height parameter with reference measurements made on WBCT. Methods: DRR generated from preoperative WBCT of 71 patients (72 feet) treated surgically for PCFD were retrospectively compared with preoperative weight-bearing XR after exclusion criteria were applied. Six radiographic measurements were performed, including Meary angle, calcaneal pitch (CPA), medial cuneiform height (MCH), AP talar–first metatarsal angle (T-1MT), talonavicular coverage (TNCA), and talar incongruency (TIA). Arch height was measured on XR, DRR, and WBCT using a validated, standardized, navicular-based index. Intraclass correlation coefficients assessed DRR intraobserver and interobserver reliability. Paired samples t tests tested differences between XR and DRR. Bland-Altman limits of agreement analysis compared DRR and XR agreement with WBCT measurements. Results: Measurements were within standard PCFD ranges on XR and DRR. All measurements demonstrated excellent intrarater reliability and good to excellent interrater agreement, consistent with previous literature on XR. No differences were found for Meary, CPA, or TNCA. Minor differences were observed for MCH, T-1MT, and TIA. DRR measurements demonstrated greater agreement with WBCT than XR measurements. Conclusion: DRR from WBCT may be a promising substitute for XR in the clinical evaluation of PCFD. Radiographic measurements made on DRR demonstrated good to excellent reliability. Although small differences were found between XR and DRR for certain measurements, DRR more accurately represented medial arch anatomy compared to gold standard WBCT data than XR. If validated as a clinical substitute, DRR could eventually obviate XR where WBCT is available. Level of Evidence: Level III, retrospective cohort study.